Ispol'zovanie sredstv batutnoj podgotovki dlja rasširenija vozmožnostej primenenija složnokoordinacionnych techniceskich dejstvij tchekvondo - Rogozhnikov, M. A.; Sergeeva, A. G. (Theory and Practice of Physical Culture, 2018)
New rules of taekwondo sport were put into effect in January 2018, with the successful technical actions in the competitive bouts now rated on a five-point scale. Successful complex coordinated technical actions are now rated by three to five points. The technique rating criteria in the Poomsae Freestyle discipline, for instance, have changed for head kicks; series of aerial kicks; and horizontal and vertical rotary-jump kicks. The article analyzes benefits of the new trampoline training tools to expand the range of the complex coordinated techniques in taekwondo.